2013
DOI: 10.1517/13543784.2013.770837
|View full text |Cite
|
Sign up to set email alerts
|

Disease-modifying osteoarthritis drugs:in vitroandin vivodata on the development of DMOADs under investigation

Abstract: It is expected that a wider range of prospective clinical studies will be embarked upon in the coming years. Trials including MRI as well as joint space narrowing (JSN) should be designed in a systematic manner, powered with sufficient numbers to demonstrate clinical benefit at different stages of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 74 publications
0
23
0
2
Order By: Relevance
“…Avocado-soybean has been shown to increase aggrecan synthesis, and to reduce catabolic and pro-inflammatory mediator production by human osteoarthritic chondrocytes . Studies of the effects of avocado-soybean on osteoarthritis reported conflicting results with respect to symptom modification (Davies et al, 2013).…”
Section: Translational Value Of the Animal Studiesmentioning
confidence: 99%
“…Avocado-soybean has been shown to increase aggrecan synthesis, and to reduce catabolic and pro-inflammatory mediator production by human osteoarthritic chondrocytes . Studies of the effects of avocado-soybean on osteoarthritis reported conflicting results with respect to symptom modification (Davies et al, 2013).…”
Section: Translational Value Of the Animal Studiesmentioning
confidence: 99%
“…Although several concerns regarding their efficacy profiles have been raised (28), it was reported that SYSADOAs may play a role as disease modifying drugs in OA (DMOADs) (41), Their efficacy profile for symptom relief in knee OA was recently reported to be good when compared to placebo in a network metaanalysis (42), while a recent randomized controlled trial (RCT) demonstrated the non-inferiority of glucosamine associated to condroitin sulphate versus celecoxib (43). The failure of SYSADOAs and other agents to show being specific treatments for OA that modify both symptoms and disease prosecution could be also ascribed to the fact that different phenotypes of OA may respond in a variable manner to different therapies.…”
Section: The Uncertainty Of Analgesic Treatment In Oamentioning
confidence: 99%
“…While no effective therapy to treat OA is yet available, recent research shows promising disease-modifying properties of several drug candidates [4][5][6]. For instance, fibroblast growth factors FGF-2 and FGF-18, transforming growth factor TGF-ÎČ, and insulin-like growth factor IGF-1 promote cartilage homeostasis promote cartilage homeostasis [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%